General and specific perceptions of procedural justice: Factors associated with perceptions of police and court responses to domestic and family violence. Issue 3 (September 2020) - Meyer, Silke; Williamson, Harley
Improving criminal justice responses to domestic and family violence is a key focus within many policy and practice reforms. The efficacy of police and court responses to domestic and family violence is central because of the role of police as first responders and courts in issuing protection orders, imposing sanctions and ensuring perpetrator cooperation and accountability. To promote compliance and satisfaction with criminal justice outcomes, a large body of research points to the role of procedural justice. This study draws on survey and administrative data from an Australian jurisdiction to examine perceptions of procedural justice in specific domestic and family violence-related encounters. Findings and implications for policy and practice are discussed.